Characterization of Silver Nano Particles Synthesized by Leaves Green Tea Extract - Neeran Obied Jasim (Journal of Global Pharma Technology, 2018)
Background and Objective: Plant extract contain biomolecules which can be a reduce metal, ions, to nanoparticles in one step n synthesis process.. Materials and Methods: green synthesis of silver nanoparticles using aqueous leaves extract of green tea and study the characters of this particles using UV -VIS spectrophotometer and SEM .Also, Investigation the antifungal activity of it. Results : silver nanoparticles were synthesized using leaf extract of green tea in present of silver nitrate and the color change to brown .UV-Vis spectrophotometer appear peak in wavelength at 420nm which is prescribed for silver nanoparticles . the microscope images by SEM, showing the size of Ag nanoparticles in range 3.6-5.3nm.Antifungal activity explain the ability of biosynthesis silver nanoparticles to inhibition the growth of yeast, C. neoformans with zone of inhibition 2.7mm compare with leaves extract in diameter 7mm.Conclusion: An extract of leaves green tea at room temperature act as reducing agent and can be used in synthesis of silver nanoparticles which have antifungal activity.Keywords: Green synthesis, Nanoparticles, Silver nanoparticles, C. neoformans.